Design and commissioning of a thermal stability test-rig for mixtures as working fluids for ORC applications. (September 2017) - Keulen, L.; Landolina, C.; Spinelli, A.; Iora, P.; Invernizzi, C.; Lietti, L.; Guardone, A.
Abstract: A novel test-rig for studying the thermal stability of mixtures as working fluids for ORC applications was designed and commissioned at the Laboratory of Compressible-fluid dynamics for Renewable Energy Applications (CREA) of Politecnico di Milano, in collaboration with the University of Brescia. The set-up is a standard one, in which a vessel containing the fluid under scrutiny is placed in a vertical oven for ~ 100 hours at a constant temperature T = T stress . During the test, the pressure P is monitored to detect thermal decomposition of the fluid. After the test, the vessel is placed in a controlled thermal bath, where the pressure is measured at different value of the temperature T, with T < T stress and T < T c ( T c critical temperature). The resulting isochoric pressure-temperature dependence is compared to that obtained before the fluid underwent thermal stress. If departure from the initial fluid behavior is observed, significant thermal decomposition occurred and a chemical analysis of the decomposition products is carried out using gas chromatography and mass spectroscopy. The novelty of the set-up is the possibility of taking samples of both liquid and vapor phases of the fluid, a capability that was introduced to study thermal decomposition of mixtures, whose composition depends on the pressure and temperature, as well as to capture the more volatile products of thermal decomposition of pure fluids and mixtures. Preliminary experimental results are reported for the pure siloxane fluid MDM (Octamethyltrisiloxane, C8 H24 O2 Si3 ).